The Occupy and Indignados movement and the importance of political context: differences between occasionals and regulars in Spain and the UK - Cristina Gomez-Roman; Jose Manuel Sabucedo (European Journal of Government and Economics (EJGE), 2016)
In this work we look into the individuals' reasons that led Occupy protesters to participate in this movement. We interviewed Occupy participants in the UK and Spain. We wanted to find out if the reasons that lead them to participate are the same in both countries. The context of the country where the demonstration was held was taken into account, as well as the differences there may be in the reasons for participation if we consider whether they are occasional or regular participants in collective protest actions. Using a two-by-two design defined by country of demonstration and the history of mobilisation (occasional vs. regular), our results show important differences in both factors. The study contributes to the literature, highlighting the importance of analysing the context where the demonstration takes place and which motives must be underlined in order to attract participants to protests.
Keywords: 330; Political context; participation motives; Occupy; Spain; UK.